Design and Construction of a Bending Test Machine Using the VDI 2222 Method and Accuracy Verification Using UTM - Bayu Prabandono; Laurentius Sumadi; Paulinus Cherlyndo Paterias; Ivo Arya Gustantia; Yanuarius Wahyu Utama; Bondan Wiratmoko Budi Santosa; Agus Kurniawan (Magister Teknik Mesin Universitas Pancasila, 2026)
Plastic material testing is conducted to determine the mechanical properties and strength characteristics of plastic materials. The selection of appropriate plastic material is a critical aspect in product design to ensure optimal strength and quality. At PT XYZ, a discrepancy was identified between the elastic modulus values stated in the material datasheet and those observed in the actual product material. Such differences can affect the fracture limit, resulting in products that do not meet design specifications. In response to this issue, a product bending test machine was proposed and designed. The VDI 2222 methodology was utilized in the design process, and testing was performed using PMMA specimens in accordance with ASTM D790 standards. Verification was conducted using the Zwick Roell Z020 Universal Testing Machine, accompanied by analytical calculations to determine the accuracy of the newly designed machine. The study resulted in alternative design options for the bending test machine based on the requirements list and calculated accuracy levels. The accuracy results showed a force accuracy of 98.63%, displacement accuracy of 58.67%, and stress accuracy of 97.34%. The significant deviation in displacement is suspected to be due to system incompatibility and additional jig components that were not perfectly perpendicular to the pressing plane, leading to measurement errors. The current prototype of the product bending test machine is considered not yet suitable for industrial applications. Further review is required, particularly in calibrating the displacement between the mechanical components and the electronic control system.